2016
DOI: 10.1111/pin.12417
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus‐positive diffuse large B cell lymphoma arising from a chronic lymphocytic leukemia: Overlapping features with classical Hodgkin lymphoma

Abstract: A small proportion of patients with chronic lymphocytic leukemia (CLL) may progress to large cell lymphoma, or Richter syndrome (RS). The large cells of RS may arise through transformation of the original CLL clone (clonally related) or represent a new neoplasm (clonally unrelated), which might be Epstein-Barr virus (EBV)-associated. We present a 61-year-old male with 5-year history of CLL who developed RS on bilateral adrenal glands. The tumor showed a vague nodular growth pattern separated by thick fibrous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…11 Our patient was diagnosed as gastrointestinal MCL after chemotherapy and antiviral treatment with entecavir. Although the presence of negative EBV during the treatment period was different from previous studies,24 our patient was found positive HBV-DNA after chemotherapy, and then he accepted 20 months of antiviral treatment. A recent study also shows that antiviral treatment can lead to a complete remission of hepatitis C virus (HCV)-associated low-grade NHL, suggesting a causative role of HCV in these tumors.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…11 Our patient was diagnosed as gastrointestinal MCL after chemotherapy and antiviral treatment with entecavir. Although the presence of negative EBV during the treatment period was different from previous studies,24 our patient was found positive HBV-DNA after chemotherapy, and then he accepted 20 months of antiviral treatment. A recent study also shows that antiviral treatment can lead to a complete remission of hepatitis C virus (HCV)-associated low-grade NHL, suggesting a causative role of HCV in these tumors.…”
Section: Discussioncontrasting
confidence: 90%
“…1 Second malignancies are frequent complications in CLL/SLL patients, and this process is commonly referred to as Richter’s syndrome (RS). About 2–8%, 0.5%, and 0.1% of CLL/SLL patients progress to diffuse large B cell lymphoma, Hodgkin’s lymphoma, and multiple myeloma, respectively. 2 Studies show that RS is commonly associated with Epstein–Barr virus (EBV),24 karyotypic changes,5 and gene mutations 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…All of these agents are orally administered and in contrast to earlier generations of antineoplastic agents are typically prescribed until there is tumor progression, i.e., patients may be treated with these agents for months or years. None of these malignancies is typically associated with EBV, although high EBV copy number in blood has been reported in some patients with chronic lymphocytic leukemia (27,28), and chronic lymphocytic leukemia may evolve into EBV-associated diffuse large B cell lymphoma or Hodgkin lymphoma (29,30). We suspect that the BTK and PI3K␦ inhibitors will impact the long-term EBV reservoir and EBV viremia.…”
Section: Discussionmentioning
confidence: 99%
“…An aggressive lymphoma known as Richter syndrome (RS) that usually arises in CLL patients might be associated with EBV reactivation [ 103 , 104 ]. In RS, the large cells may represent a new neoplasm or they could emerge through the transformation of the original CLL clone, which might occur due to the EBV reactivation [ 105 ]. The association between EBV reactivation and the increased risk of RS development in CLL patients during immunosuppressive therapy was also reported [ 106 ].…”
Section: CMV and Ebv Infection Impact In Patients With Hematologicmentioning
confidence: 99%